P58 Real world hospice research: challenges and opportunities. (1st October 2013) - Russell, Sarah; Chadwick, Sharon; Hodell, Kate; Barbara, Miller; Nmeth, Erzsi; Taylor, Ros; McLaughlin, Kimberley; Woodwark, Cate
Abstract : Compassionate evidence-based practice, collecting data and building evidence is fundamental to hospice care. The Hospice of St Francis research strategy provides a real world pragmatic effective approach to research evidenced based care in a medium sized hospice. Challenges: Research governance and credibility as a small organisation Time to reflect, discuss and put into practice evidenced based care Being a Researcher Practitioner in the workplace Realistic research with Universities and other research organisations. Using research to disseminate and influence care beyond the hospice walls Solutions and Opportunities: Research strategy, governance and register of all research, audit and service evaluation activity reported to Clinical Governance and Clinical Leads forum. Collaborative research and governance with Institutes of Higher Education and individual researchers wanting to access our hospice as a research site. Research Interest Forum: 2 monthly multi professional forum to discuss issues as researchers in practice and evidence based practice clinicians. Journal Club: Quarterly forum to discuss articles of interest and relevance to practice Think Tank: Monthly multi professional forum to share feedback from conferences and practice initiatives. Case and Care Reflections: monthly forums reflecting on clinical care. Clinical Nurse Specialist Continuous Professional Development Programme: 2 monthly forum delivered by Associate Specialist in palliative care. Schwartz rounds to stimulating discussion and reflection about care Publications and dissemination strategy. A shared passion for real world research. "Hospices must meet a range of challenges: collecting better data, developing a better understanding of those who needs will dominate future decades, and establishing a robust evidence base for new services" (Calanzani 2013). The Hospice of St Francis whole system approach to real world research makes a difference to care and offers possibilites for other similar sized organisations